1996
DOI: 10.1007/bf01254472
|View full text |Cite
|
Sign up to set email alerts
|

Different thallium-201 single-photon emission tomographic patterns in benign and aggressive meningiomas

Abstract: To evaluate the possibility of preoperatively obtaining an index of aggressiveness for intracranial meningiomas, we prospectively studied 22 patients with computed tomographic or magnetic resonance imaging evidence of meningeal tumour, using single-photon emission tomography (SPET) of the brain and thallium-201 (201Tl). On a brain-dedicated SPET scanner, a rapid acquisition protocol with early, short scans was started simultaneously with the intravenous administration of 111 MBq 201Tl, covering the initial int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The involvement of at least three cerebral lobes by an infiltrative tissue, the lack of a single discrete mass and pathological confirmation of diffuse glioma (WHO grade IV) indicate the diagnosis. However, the imaging features may also be present in CNS inflammatory diseases, vasculitis, encephalitis, leukoencephalopathies, especially when there is no obvious mass effect (2,(5)(6)(7)(8)(9)(10). While cases of demyelinating diseases mimicking gliomas are well represented in the literature (11,12), the opposite is a rather rare occurrence, mainly reported in the pediatric (13)(14)(15) or young (16) age.…”
Section: Discussionmentioning
confidence: 95%
“…The involvement of at least three cerebral lobes by an infiltrative tissue, the lack of a single discrete mass and pathological confirmation of diffuse glioma (WHO grade IV) indicate the diagnosis. However, the imaging features may also be present in CNS inflammatory diseases, vasculitis, encephalitis, leukoencephalopathies, especially when there is no obvious mass effect (2,(5)(6)(7)(8)(9)(10). While cases of demyelinating diseases mimicking gliomas are well represented in the literature (11,12), the opposite is a rather rare occurrence, mainly reported in the pediatric (13)(14)(15) or young (16) age.…”
Section: Discussionmentioning
confidence: 95%
“…However, the tumors with high initial uptake of 201 TlCl may not be malignant if the washout is rapid. Tedeschi et al found the early temporal pattern of T1-201 concentration in intracranial meningiomas is probably related to their biologic aggressiveness, 11 and Sugo et al suggested that dynamic 201 TlCl SPECT was useful in distinguishing malignant brain tumors from benign tumors. 23 Our current study revealed 13 N-NH 3 was unable to differentiate grade I from grade II meningiomas.…”
Section: Discussionmentioning
confidence: 98%
“…[11][12][13] There are 2 chemical forms of ammonia (NH 3 and NH 4 ϩ ) in the blood. The relative proportion of NH 3 and NH 4 ϩ in blood is determined by the pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…201 Tl was among the first single-photon emitting radiotracers studied in meningioma. Its uptake pre-operatively has been proposed to differentiate meningiomas with different biological behaviors, while tracer retention by a lesion correlated with its malignant potential (Jinnouchi et al, 1993;Tedeschi et al, 1996). Nevertheless, later reports did not verify any correlation between 201 Tl uptake and PCNA labeling index in meningiomas, dissimilar to gliomas (Gungor et al, 2000).…”
Section: Assessment Of Meningiomas: Differentiation Between Typical Amentioning
confidence: 90%